Uji Kadar Hara Nitrogen, Fosfor, dan Kalium pada Kompos Pelepah Kelapa Sawit dengan Pemberian Trichoderma harzianum dan Kotoran Sapi - Sakiah, Sakiah; Dibisono, Muhammad Yusuf; Susanti, Susanti (Politeknik Negeri Lampung, 2019)
Palm oil fronds is one of the wastes originating from the oil palm industry which are difficult to decompose. The right decomposer application is one of the success keys, if the oil palm fronds are processed into compost hence the expected quality of compost is achieved. This research aim was to determine the quality of oil palm fronds compost with Trichoderma harzianum and cow dung application based on N, P, K nutrients content, C-organic and C/N compost ratio. The research design used was factorial complete randomized design, the first factor was cow dung (0 kg, 1 kg, and 2 kg) and the second factor was Trichoderma harzianum (0 g, 50 g, and 100 g). Research observations included compost temperature, compost pH, N, P, K, C-organic, and C/N compost ratios. The results showed that the application of cow dung, Trichoderma harzianum and their interactions had no significant effect on N, P, K nutrient content, C-organic, and C/N compost ratios, as a whole, the observed compost characteristics met compost criteria based on SNI 7030-200.